The Impact of Secure Tenure on Women's Participation in Agricultural Households Decision-Making: Has It Been Equal? - Wartiningsih, Wartiningsih; Andiojaya, Agung (University of Jember, 2024)
The empowerment of women within the agricultural sector constitutes a pivotal factor for the sustainability of farming practices. A key facet of women's empowerment lies in their capacity to make decisions, encompassing choices both for personal matters and those pertaining to their families. Land ownership is posited as a significant catalyst fostering individual decision-making prowess. However, Indonesia grapples with challenges concerning the attainment of parity in land ownership between genders. This research endeavors to scrutinize the repercussions of land ownership, particularly secure tenure, on individuals' participation in decision-making processes. Additionally, it seeks to discern disparities in decision-making participation between men and women. The data underpinning this study emanate from individual-level information extracted from the 2021 integrated agricultural survey, yielding a robust dataset with 635.235 observations of the adult population. The findings of this investigation illuminate a positive correlation between land ownership and heightened participation in decision-making. Nonetheless, when dissected through the lens of gender, it becomes apparent that women exhibit a propensity for diminished participation in decision-making related to agricultural endeavors, relative to their male counterparts. Remarkably, women endowed with secure tenure tend to manifest a proclivity toward reduced involvement in decision-making processes. Despite this observed trend, it is noteworthy that targeted agricultural training programs hold promise for amplifying the participation of women in decision-making roles. This underscores the potential for interventions aimed at bridging existing gender differentials in decision-making within the agricultural domain.